Degenerate Anisotropic Differential Operators and Applications. (23rd February 2011) - Agarwal, Ravi; O'Regan, Donal; Shakhmurov, Veli
Abstract : The boundary value problems for degenerate anisotropic differential operator equations with variable coefficients are studied. Several conditions for the separability and Fredholmness in Banach-valuedL p spaces are given. Sharp estimates for resolvent, discreetness of spectrum, and completeness of root elements of the corresponding differential operators are obtained. In the last section, some applications of the main results are given.